(untitled) (Communications in Computational Physics, 2018)
In this paper, we first develop the mathematical modeling equations for wave propagation in several transformation optics devices, including electromagnetic concentrator, rotator and splitter. Then we propose the corresponding finite element time-domain methods for simulating wave propagation in these transformation optics devices. We implement the proposed algorithms and our numerical results demonstrate the effectiveness of our modeling equations. To our best knowledge, this is the first work on time-domain finite element simulation carried out for the electromagnetic concentrator, rotator and splitter.